Prokaryotic community diversity, assembly processes, and potential metabolic pathways of a hexanoic acid-producing microbiota constructed from Chinese baijiu fermentation pit mud - Xiaolong Hu; Mingdong Deng; Xinyu Zhang; Yueqi Wang; Wenyou Zhu; Tian Zeng; Wei Zheng; Yaping Wang; Min Gou; Zhaoxiang Wang (Bioresource Technology, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Performance optimization and application advances of cellulose-based triboelectric materials for high-humidity environments - Yakun Mou; Yuhang Qiu; Mingyang Li; Yaping Zeng; Yanniu Xu; Dengjun Lu (Carbohydrate Polymers, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Beyond static imaging: A dynamic decision paradigm for robust array-SAR in diverse sensing scenarios - Xiangdong Ma; Xu Zhan; Xiaoling Zhang; Yaping Wang; Jun Shi; Shunjun Wei; Tianjiao Zeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Bio-inspired spore-like CoSe2@CNFs heterostructure enabling ultra-stable and high-rate sodium-ion batteries - Enze Ren; Yu Chen; Yaping Zeng; Zhenyao Wang; Wanquan Liu; Heng Wang; Jianrong Xiao; Liu Wang (Chemical Engineering Journal, 2025)

Research progress on properties and applications of triboelectric nanogenerators based on cellulosic triboelectric aerogels - Yuhang Qiu; Yakun Mou; Xunxiao Wu; Yaping Zeng; Yanniu Xu; Mingyang Li; Dengjun Lu (Chemical Engineering Journal, 2025)

Screening of siderophore-producing bacteria isolated from marine environments - Xiang Zeng; Guangyu Li; Yaping Du; Tong Yu; Qiliang Lai; Liping Wang; Zongze Shao (Acta Oceanologica Sinica, 2025)

Eutrophication mitigates Cu-induced inhibition on growth and photosynthetic performance in the marine diatom Thalassiosira weissflogii - Shumin Zeng; Xiangyu Li; Linrong Peng; Juntian Xu; Zhenzhen Li; Yaping Wu (Marine Pollution Bulletin, 2025)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

Biochanin A Attenuates Psoriasiform Inflammation by Regulating Nrf2/HO-1 Pathway Activation and Attenuating Inflammatory Signalling - Yaping Lv; Yingsheng Xu; Songchun Liu; Xianjing Zeng; Bin Yang (Cell Biochemistry and Biophysics, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Detrital zircons record the provenance and source-to-sink process in the northwestern margin of the South China Sea - Heqi Cui; Ce Wang; Ming Su; Yaping Lei; Letian Zeng; Junmin Jia (Frontiers in Marine Science, 2024)
The northwestern continental margin of the South China Sea, extending from the broad shelf and canyon-growth slope across the Xisha Trough, represents a relic crustal rift that eventually connects to the abyssal plain. However, the provenance and source-to-sink process of sediments in this special topography remains unclear. In this study, we present the detrital zircon U-Pb geochronology of surface sediments from the northwestern margin of the South China Sea to identify the sediment provenance, track the transport pathway, and understand the source-to-sink process in this margin. The results showed that detrital zircons exhibit a wide range of U-Pb ages from 3,062.9 to 41.5 Ma and are characterized by peaks centered on 140–154 Ma, 240–258 Ma, 425–452 Ma, and 738–991 Ma. Statistical analysis indicated that the clastic sediments on the shelf closely resemble those sourced from the Pearl River system. Conversely, sediments on the slope and abyssal plain demonstrated characteristics indicative of multiple sources, primarily originating from the Pearl River, with a minor contribution from the Red River. Further quantitative study revealed a progressive increase (from 8.2% to 43.2%) in the prevalence of Red River-derived sediments with ascending water depth on the shelf and slope, whereas sediment influx in the deepest sector remains predominantly sourced from the Pearl River. This study emphasizes the controls of topography and currents in modulating the transportation of coarse-grained and fine-grained sediments within the source-to-sink system and provides a favorable solution for reconstructing the sedimentary process in continental margins.

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

Holocene provenance evolution of the northern South China Sea inferred from detrital zircon U-Pb geochronology and Hf isotopes - Ce Wang; David A. Foster; Ming Su; Yaping Lei; Letian Zeng; Heqi Cui (Global and Planetary Change, 2023)

Highly efficient catalytic degradation of dicamba using Fe3O4/montmorillonite composite: Mechanism and toxicity assessment - Yu Ouyang; Guangyong Zeng; Wei Zhu; Xuemei Yao; Mengyun Yang; Xiuyu Long; Jie Zheng; Yaping Tao; Yaocheng Deng; Chunxia Ding (Process Safety and Environmental Protection, 2023)

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Environmental-friendly hydrochar-montmorillonite composite for efficient catalytic degradation of dicamba and alleviating its damage to crops - Chunxia Ding; Guangyong Zeng; Yaping Tao; Xiuyu Long; Daoxin Gong; Nan Zhou; Rongying Zeng; Xiangying Liu; Yaocheng Deng; Mei-E Zhong (Science of The Total Environment, 2023)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

Origin of crystal dolomite and its reservoir formation mechanism in the Xixiangchi Formation, Upper Cambrian in Southeastern Sichuan basin - Xuefei Yang; Zisang Huang; Xingzhi Wang; Yaping Wang; Ke Li; Deming Zeng (Carbonates and Evaporites, 2019)

Arabidopsis glutamate:glyoxylate aminotransferase 1 (Ler) mutants generated by CRISPR/Cas9 and their characteristics - Yaping Liang; Xiuying Zeng; Xinxiang Peng; Xuewen Hou (Transgenic Research, 2018)

Removal of Trace As(V) from Water with the Titanium Dioxide/ACF Composite Electrode - Liang Peng; Yaping Chen; Hong Dong; Qingru Zeng; Huijuan Song; Liyuan Chai; Ji-dong Gu (Water, Air, & Soil Pollution, 2015)

Removal of trace Cd(II) from water with the manganese oxides/ACF composite electrode - Yaping Chen; Liang Peng; Qingru Zeng; Yang Yang; Ming Lei; Huijuan Song; Liyuan Chai; Jidong Gu (Clean Technologies and Environmental Policy, 2015)

Lack of mtDNA control region variation in Hainan Eld's deer: Consequence of a recent population bottleneck? - Junfeng Pang; A. Rus Hoelzel; Yanling Song; Zhigao Zeng; Yaping Zhang (Conservation Genetics, 2003)